Multiculturalidade e voluntariado educativo: o que isso tem a ver? - Motta, Marcela Moura (2014)
The main purpose of this study was to search into the way the actions of the participants of an educational voluntary project at a private school in the city of São Paulo could develop the multicultural study in activities performed at a Children and Adolescents Center, along with students from public schools and critically discuss how the multicultural study has been evolved. In other words, I intended to look over the possibility of meanings realignments. This study was based on the Social- Historical-Cultural Theory (VYGOTSKY, 1934/1987, 1930-35/1988; LEONTIEV, 1977, 1978a; ENGESTRÖM, 1987, 1999a), grounded in the Argumentation studies (LIBERALI, 1999-2013) as well as in the multicultural study (SANTOS, 2008) which deals with the relationship among the subjects in unremitting connection in the production of multiple meanings, contributing to the origin of senses and meanings. This has been a critical research of collaboration PCCol (MAGALHÃES, 2002; 2004; 2007), whose researchers assume that their role evolves not only observing and describing contexts, but they also interfere with them, by understanding and transforming them into a single movement. It is the development of a creative work in partnership in which there can be the generation of reframing meanings, focusing on the multicultural study. The corpus analysis focused on discourses of students of a private school, belonging to high social class, located in the west zone of São Paulo; students from public schools; the teacher-researcher, who is a teacher at a private school; and a robotics instructor whose employment is established with the Congregation that holds the location where the classes took place. Data were registered through audio recordings during ten robotics classes, taught by an instructor and led at the Children and Adolescents Center, located in a neighborhood which has some of the features of a similar one in the west zone of São Paulo, where everyone gathered to attend the robotics activities activities which were part of the educational volunteering project of the private school during the period from March 11, 2013 to June 24, 2013. The discussion of the data highlighted the multicultural view built among the participants. However, it also demonstrated that the multicultural study, as defined in this research, does not always occur due to the lack of articulation throughout discussions and negotiations